Physiological and pathological covariates of persistent concussion-related fatigue: results from two regression methodologies. (21st March 2019) - Mollayeva, Tatyana; Stock, David; Colantonio, Angela
ABSTRACT: Background : Fatigue severity in persons with mild traumatic brain injury (mTBI) has received little research attention, despite its typically positively skewed nature. Investigation of covariates across a range of fatigue severity may provide insight into important contributors. Objective : To assess the relative significance of a priori-hypothesized covariates of physiological and pathological (mental and physical) fatigue in persons with mTBI/concussion, applying ordinary least squares (OLS) and quantile regression (QR) approaches. Methods : We conducted a cross-sectional investigation in 80 participants with mTBI/concussion (mean age 45.4 ± 10.1 years, 59% male). The fatigue severity scale (FSS) was used as an outcome measure. Predictors of this outcome, grouped into physiological and pathological models of fatigue were assessed using OLS and QR. Results : The mean total FSS score was 46.13 ± 14.59, and the median was 49 (interquartile range 37–57), demonstrating positive skewness. Fatigue severity was associated with variables within the mental, psychological and psychiatric domains at different levels of the fatigue score distribution. Conclusion : Results highlighted that some covariates had a significant impact on the FSS total score at non-central parts of its distribution, while others exhibited significant impact across the entire distribution. Addressing covariates of fatigue across the severity continuum can enhance research and clinical management.